(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
Shale, sandstones, limestones, and dolomites are geological formations that play key roles in forming and trapping hydrocarbon systems. The knowledge of GR signature of clean shales, limestones and sandstones is significant for more precise identification of formations. This study aims to propose a statistical technique for determining the gamma ray log signature of clean shales, sandstones, limestones, and dolomites. This approach of combines the GR log statistical processing method and the bootstrap mean estimation method. The case study has helped to determine Benin’s offshore sedimentary basin clean formations GR signature at the scale of the petroleum block 1. The results show that Benin’s block 1 clean shale GR signature is 122.57 GAPI with a confidence interval of [116.41GAPI; 128.26GAPI] while its clean limestone or sandstone GR signature is 16.63 GAPI with a confidence interval of [12.84GAPI; 20.51GAPI]. As a result, over the qualitative analysis of a block 1 well GR log data, the clean shale and clean sandstone baselines to be used have to correspond to these GR signatures. Moreover, these clean formations GR signatures have to be taken into account over formations shale volume computation.